UNDERSTANDING THE LIVED EXPERIENCES OF SYSTEMS PLUS COLLEGE FOUNDATION OF NURSING STUDENTS IN CARING OF GERIATRIC CLIENTS: A DESCRIPTIVE-PHENOMENOLOGICAL STUDY - Berek, Pius A L; Orte, Christian Jay S.; Angeles, Jackilou G.; Canlapan, Jinia T.; Ramos, Jennalyn J.; Viray, Leandro M.; Bautista, Regie A.; Villanueva, John Christian V.; Maniago, Jestoni D. (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Objective: The study aimed to explore, analyze and reflect on the lived experiences of Systems Plus College Foundation (SPCF) College of Nursing Students in caring of geriatric clients. Method: Descriptive-phenomenological method was employed with five (5) participants captured via convenience sampling with experience in caring of geriatric clients. Semi-structured aide memoire was used and Collaizzi’s phenomenological inquiry was employed in analyzing the data. Results: It showed that nursing students make a balance between the theory and practice and emphasized the active listening and therapeutic communication as essentials for taking care of geriatric clients. Conclusion: The study surfaced that student-nurses done their best to manage their fear and anxiety and be positive in taking care of geriatric clients.